2022
DOI: 10.1007/s12525-021-00505-z
|View full text |Cite
|
Sign up to set email alerts
|

No matter what the name, we’re all the same? Examining ethnic online discrimination in ridesharing marketplaces

Abstract: Sharing marketplaces emerged as the new Holy Grail of value creation by enabling exchanges between strangers. Identity reveal, encouraged by platforms, cuts both ways: While inducing pre-transaction confidence, it is suspected of backfiring on the information senders with its discriminative potential. This study employs a discrete choice experiment to explore the role of names as signifiers of discriminative peculiarities and the importance of accompanying cues in peer choices of a ridesharing offer. We quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Another interesting point, which at the same time corroborates the analysis with the studies found in the literature, was in relation to the provision of passenger information, such as address of origin and destination, to the driver only after accepting the trip as [Miroslav Tushev and Mahmoud 2021], citeGe2016, [Brown 2019] and [Abramova 2020]. However, this was a point where we found opinions differing from the user platform.…”
Section: Study Results and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Another interesting point, which at the same time corroborates the analysis with the studies found in the literature, was in relation to the provision of passenger information, such as address of origin and destination, to the driver only after accepting the trip as [Miroslav Tushev and Mahmoud 2021], citeGe2016, [Brown 2019] and [Abramova 2020]. However, this was a point where we found opinions differing from the user platform.…”
Section: Study Results and Discussionsupporting
confidence: 88%
“…Digital discrimination in shared services has been addressed from different aspects, but the main one found in the literature was diagnosis as in [Abramova 2020] [Brown 2019] [Ge 2018]. But approaches were also found from the aspect of the information system where the interest was divided into identifying biases in the algorithms adopted Shared ride service platforms, with the aim of reducing discrimination on the part of drivers, began sending the least amount of information about the passenger to drivers when distributing the ride request.…”
Section: Study Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many factors that influence the trust between unknown individuals are the names from different cultures as well as the role of gender. The author states that "in ridesharing, participants with European descent names are reluctant to male peers with Middle Eastern descent names, and the nature of this discrimination is taste-based" (Abramova, 2022).…”
Section: General Research Articles 1 -Platform Postingsmentioning
confidence: 99%
“…In line with these dual objectives, an emerging literature has started to document discrimination on different platforms of the sharing economy (for a recent review, see Ref. 16 ). In their seminal work, Edelman et al 17 found that Airbnb users with stereotypically African American names were 16% less likely to have their requests for accommodation approved than otherwise identical users with stereotypically White American names (see also Ref.…”
Section: Introductionmentioning
confidence: 99%